Penerapan Inovasi di Institusi Pendidikan Melalui Aplikasi PIESA di MA YPPA Cipulus - Risa Destriani; Nunung Nurul Kamilah; Dwi Ajeng Maulidya Makalao (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2026)
This study examines the process of developing information technology-based innovations at MA YPPA Cipulus through the implementation of the PIESA (Academic System Education Innovation Platform) application. Madrasahs, as formal educational institutions with an Islamic character, are now faced with the demands of digital transformation that can no longer be postponed. Using a descriptive qualitative research approach with data collection techniques such as in-depth interviews, observations, and documentation studies, this study found that PIESA is able to integrate academic management, digital attendance, and communication between stakeholders in a single platform. The implementation results show a significant increase in administrative efficiency and positive changes in the institution's work culture. This study contributes to the literature discourse on technology adoption in Islamic boarding school-based educational institutions, which has so far been limited.